Wanted - Schow, Betsy, 1981- (Schow, Betsy, 1981- Storymakers series., 2017)
Rexi Hood, the daughter of Robin Hood, is proud to be an outlaw, but ever since they teamed up to fight the wickedest witch, she and Princess Dorothea of Emerald have been inseparable due to a curse. If Rexi doesn't figure out how to break the curse, she'll be wiped from the pages of Story.